Human-nature relationships through the lens of reciprocity: Insights from Indigenous and local knowledge systems - Teixidor-Toneu, Irene; Fernandez-Llamazares, Alvaro; Abel, Ricardo Alvarez; Batdelger, Gantuya; Bell, Elicia; Caillon, Sophie; Cantor, Mauricio; Correia, Joel E.; Diaz, Sandra; Fisk, Jonathan; Greene, Alexander; Greening, Spencer; et al. (My University, 2025)
In the context of climate change, biodiversity decline and social injustice, reciprocity emerges as a way of living and being in this world that holds transformative potential. Concepts of reciprocity vary and are enacted in specific cultural practices grounded in Indigenous and local knowledge systems. This editorial synthesises first-hand evidence of how practising reciprocity can result in positive reciprocal contributions between people and nature. It also offers a theoretical justification of why considering reciprocity can lead to more equitable, inclusive and effective conservation and sustainability policy and practices, contributing to curving the colonial baggage of academic inquiry and development action. Nurturing reciprocal relations between people, especially between academics and Indigenous Peoples and local communities, is a necessary first step to identifying pathways whereby living in harmony with nature can be achieved. En el contexto actual de cambio climático, declive de la biodiversidad e injusticias sociales, la reciprocidad emerge como una forma de vivir y ser en este mundo con potencial transformador. Los conceptos de reciprocidad son diversos y se materializan en prácticas culturales específicas basadas en sistemas de conocimiento Indígenas y locales. Este artículo editorial sintetiza evidencia de cómo las prácticas de reciprocidad pueden dar lugar a contribuciones recíprocas positivas entre las personas y la naturaleza. El artículo también ofrece una justificación teórica de por qué la consideración de la reciprocidad puede conducir a políticas y prácticas de conservación y sostenibilidad más equitativas, inclusivas y eficaces, contribuyendo a reducir el bagaje colonial de la investigación académica y las estrategias de desarrollo sostenible. Fomentar las relaciones recíprocas entre personas, especialmente entre académicos y pueblos Indígenas y comunidades locales, es un primer paso necesario para identificar vías que permitan vivir en armonía con la naturaleza.
Keywords: indigenous and local knowledge; reciprocal relations; reciprocity; social-ecological systems